1960
DOI: 10.1507/endocrj1954.7.284
|View full text |Cite
|
Sign up to set email alerts
|

On the Reaction of Sex Hormones and Related Compounds With Metals in Ethanolic Solutions by Spectrophotometry

Abstract: Hormone-related substances 1) phenylthiourea: well-known substances to chelate intensively with copper 2) cholesterol 3) oleic acid 4) lecithin 5) phenol B

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1968
1968
1979
1979

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…
The author and co-worker (ITABASHI and ISHIDA, 1957) found the highest concentration of copper in the swine ovary during estrus.The author (ITABASHI, 1959(ITABASHI, , 1960 also found that estrogen and androgen were able to form a complex with metals including copper, judging from a significant shift of their wave length of maximum absorption in ethanolic solution after addition of the metals.In the present experiment, the reaction of progestin and related compounds with metals was studied.
Materials and MethodsMetals tested were Cu, Ni, Co, Mn, Fe (Fe++ and Fe+++) in the form of their sulphates, except Fe+++ which was used in the form of iron alum. Ultraviolet absorption spectra were measured by HITACHI Model ESP-2 A spectrophotometer, equipped with quartz cuvettes, 1cm thickness.

In order to make the effect of metals on the spectra of the steroids, the absorption spectra of ethanol, ethanol with metal, ethanolic solution of the steroids and of the steroid solution with metal were determined.

Given volume of ethanol was placed in the Cuvett I and II, and the same volume of an ethanolic solution of the steroids was put in the Cuvett III.

…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…
The author and co-worker (ITABASHI and ISHIDA, 1957) found the highest concentration of copper in the swine ovary during estrus.The author (ITABASHI, 1959(ITABASHI, , 1960 also found that estrogen and androgen were able to form a complex with metals including copper, judging from a significant shift of their wave length of maximum absorption in ethanolic solution after addition of the metals.In the present experiment, the reaction of progestin and related compounds with metals was studied.
Materials and MethodsMetals tested were Cu, Ni, Co, Mn, Fe (Fe++ and Fe+++) in the form of their sulphates, except Fe+++ which was used in the form of iron alum. Ultraviolet absorption spectra were measured by HITACHI Model ESP-2 A spectrophotometer, equipped with quartz cuvettes, 1cm thickness.

In order to make the effect of metals on the spectra of the steroids, the absorption spectra of ethanol, ethanol with metal, ethanolic solution of the steroids and of the steroid solution with metal were determined.

Given volume of ethanol was placed in the Cuvett I and II, and the same volume of an ethanolic solution of the steroids was put in the Cuvett III.

…”
mentioning
confidence: 99%
“…The author (ITABASHI, 1959(ITABASHI, , 1960 also found that estrogen and androgen were able to form a complex with metals including copper, judging from a significant shift of their wave length of maximum absorption in ethanolic solution after addition of the metals.…”
mentioning
confidence: 99%